Revisiting government expenditure and private investment nexus: an ARDL approach - Idowu, Obakemi Funsho; Okiri, Inyang John; Olarewaju, Hassan Ismail (Penerbit Universiti Kebangsaan Malaysia, 2020)
This paper re-examines the nexus between government expenditure and private investment in Nigeria over the period of 1981-2016. The study is rooted on Jorgenson’s theory of investment, the Samuelson’s version of the flexible accelerator theory and Keynesian-classical crowding-in/crowding-out theory of investment. The resulting empirical models comprise three equations; one each for private investment (PI), private domestic investment (PDI) and foreign direct investment (FDI). The study employed Autoregressive Distributed Lag technique to estimate the models. From the study, government expenditure showed positive impact on private investment in Nigeria. Our specific findings showed that: Federal government’s capital expenditure (CAEX) showed positive and significant impact on both PI and PDI in the long run: a N1.00 billion each increase in CAEX increases PI and PDI by N0.12 and N0.238billion respectively. CAEX showed negative but insignificant impact on FDI in both short and long run. State government’s capital expenditure (SCEX) showed positive and significant impact on PI: A N1.00 billion increase in SCEX increases PI by N0.27 billion. Federal government’s recurrent expenditure (REEX) showed positive and negative impact on FDI and PI respectively: A N1.00 billion increase in REEX increases FDI by N1.27 billion, and reduces PI by N0.28 billion. Our findings imply that, if the objective of government policy is to raise private investment or private domestic investment, then both the Federal Government and state governments should boost their capital expenditure.